THE EFFECT OF TWO LEVELS OF FEEDING ON THE YIELD AND QUALITY OF ALPACA FIBRE - Franco F., Francisco (2009)
The present study was carried out at the IVITA-Maranganí Experimental Station to evaluate the effect of two levels of feeding on the yield and quality of alpaca fibre.Twelve young male alpacas were used. A pre experimerntal phase was conducted for the adaptation of the animals to the balanced diet and an experimental phase with four periods was considered: Periods I and III of 28 days each were used to level body condition; in period II the animals were submitted to treatment T1 and T2, receiving 0.73 and 1.23 times the maintenance requirement for 84 days; and in period IV the animals of T1 were shifted to T2 and vice versa for another 84 days. In periods II and IV, fiber samples were taken from a 100 cm2 area on the right mid rib area, and was measured the yield, diameter (D), length (L), volume (V), L/D ratio and the contribution of L, D and (D)(L) on fibre volume. T2 was statistically superior to T1 (p<0.05) in fibre yield (5.22 vs. 4.43 g/100 cm2), D (25.75 vs. 23.97 μ), L (319.6 y 294.7 μ/d) and V (162.8 vs. 132.95 x 10-3 μ/d respectively) while the L/ D ratio was similar in both treatments. D, L and (D)(L) contributed with 68.6, 27.2 and 4.2% to fibre volume, respectively. It is concluded that the feeding levels in the alpaca influenced both the yield and volume of fibre, and that the contribution of D in the fibre volume resulted higher than the L contribution.